Corticosteroid therapy in refractory shock following cardiac arrest: a randomized, double-blind, placebo-controlled, trial. Issue 1 (December 2016) - Donnino, Michael; Andersen, Lars; Berg, Katherine; Chase, Maureen; Sherwin, Robert; Smithline, Howard; Carney, Erin; Ngo, Long; Patel, Parth; Liu, Xiaowen; Cutlip, Donald; Zimetbaum, Peter; et al.
Abstract Background The purpose of this study was to determine whether the provision of corticosteroids improves time to shock reversal and outcomes in patients with post-cardiac arrest shock. Methods We conducted a randomized, double-blind trial of post-cardiac arrest patients in shock, defined as vasopressor support for a minimum of 1 hour. Patients were randomized to intravenous hydrocortisone 100 mg or placebo every 8 hours for 7 days or until shock reversal. The primary endpoint was time to shock reversal. Results Fifty patients were included with 25 in each group. There was no difference in time to shock reversal between groups (hazard ratio: 0.83 [95 % CI: 0.40–1.75], p = 0.63). We found no difference in secondary outcomes including shock reversal (52 % vs. 60 %, p = 0.57), good neurological outcome (24 % vs. 32 %, p = 0.53) or survival to discharge (28 % vs. 36 %, p = 0.54) between the hydrocortisone and placebo groups. Of the patients with a baseline cortisol < 15 ug/dL, 100 % (6/6) in the hydrocortisone group achieved shock reversal compared to 33 % (1/3) in the placebo group (p = 0.08). All patients in the placebo group died (100 %; 3/3) whereas 50 % (3/6) died in the hydrocortisone group (p = 0.43). Conclusions In a population of cardiac arrest patients with vasopressor-dependent shock, treatment with hydrocortisone did not improve time to shock reversal, rate of shock reversal, or clinical outcomes when compared to placebo. Clinical trial registration Clinicaltrials.gov:NCT00676585, registration date: May 9, 2008.